Silk, mohair, cashmere and other luxury fibres - Franck, Robert R. (CRC Press ; Woodhead Pub., 2001)
Although none of the luxury fibres, including silk, is produced in large quantities, their particular and unique qualities of fineness, softness, warmth and pleasurable handle mean that they occupy a very important place in the luxury apparel and fine furnishing trades. This book covers all aspects of the growth, physical characteristics, production, marketing and consumption of silk, mohair, cashmere, camelhair, Alpaca, Llama, Vicuna, Guanaco, Yak and Musk Ox fibres. The image of these fabrics is of course all-important, and the book describes in detail those rare occasions when a lower price.
Published in association with the Textile Institute.
Keywords: Textile fibers.; Textile fabrics.; elektronické knihy; electronic books